Enhancing Temporomandibular Disorders Education for Initial Care Clinicians Through Interprofessional Education - James Hawkins; Ronald Cervero; Steven J. Durning (Association of American Medical Colleges, 2024)
Introduction Temporomandibular disorders (TMDs) are common musculoskeletal pain conditions that can significantly impact daily activities such as eating, talking, breathing, intimacy, and expressing emotion. TMDs are often complex and multifactorial, and many patients experience overlapping pain conditions, sleep difficulties, and mental health challenges. The National Academies of Sciences, Engineering and Medicine (NASEM) has called for improved TMD education and training for health professionals, as current training opportunities are limited. Methods To prepare health professionals to care for patients who have a TMD, we designed a 5-hour, interactive, module-based curriculum aligned with the 2020 NASEM recommendations. The four-part module set addresses TMD physiology and pathophysiology, assessment, diagnosis, and management. Instructional methods are founded on the Cognitive Theory of Multimedia Learning and include engaging videos, clinical evaluation and education tools, and interactive digital simulation scenarios. Results Thirty learners from diverse health professional backgrounds (medicine, dentistry, physician assistant, nursing, physical therapy) participated. Multiple-choice question assessments and pre/post retrospective survey scores demonstrated enhanced knowledge (M = 2.9 vs. M = 4.2, p < .001) and perceived competence (M = 1.9 vs. M = 3.4, p < .001), respectively. Encouragingly, all participants indicated applicability to their clinical practice. Discussion Our modules offer educators and clinicians a valuable resource to improve TMD knowledge and facilitate best practices. Supplementary resources included in the curriculum are conducive to clinical implementation, fostering improved clinician assessment and patient education.